Metodología para el cálculo de radiación solar a través de fotografías satelitales visibles e infrarrojas, caso práctico en la región sur del Ecuador. - Luna Jaramillo, Luis Gustavo (2014)
The Solar radiation plays a very important and essential roll to the technology and social context in the World, as the knowledge of the energy which is transferred by the Sun to the Earth in quantity is very important as with it we can build technology to collect solar energy and transform into thermic and electric, which would develop growth to the society. This thesis work has been called “METODOLOGY TO CALCULATE THE SOLAR RADIATION TROUGH SATELLITE PHOTHOGRAPS VISIBLE AND INFRARRED” Which was carried out to comply with the University requirements to obtain an electro mechanic engineer degree. So it is necessary to the application of the software programs that help to calculate solar radiation with the purpose of obtaining reliable data or information to make a series of technologic activities and studies of how the Sun energy is transferred to the Earth without using weather stations and sic imply with the main objectives of the present research work as: Develop a methodology to calculate data of the radiation through satellite photographs visible and infrared, which are validated by the weather stations on the south region of Equator.